Surgical Technique for Femoral Intramedullary Bent Nail Removal: A Case Report and Review of the Literature - Amouzadeh Omrani, Farzad; Panjehshahi, Ali; Alaedini, Melika; Ghanbari, Naser; Jamali, Seyed Mojtaba (Student Research in Translational Medicine, 2021)
A 21-year-old male patient was admitted with a severe right thigh deformity following a car accident. He experienced a previous history of Intramedullary interlocking femoral nail three years ago. The neurovascular examination was normal. The radiologic evaluation revealed a bent nail with 105° angular deformity in the sagittal plane. With a lateral approach to the apex of the fracture site, the Bent nail was cut by an 8mm cobalt drill, two parts of nail extracted; then fixation was performed by a new intramedullary interlocking nail and autogenous cancellous graft. The fracture healed properly without any complication 6 months after corrective surgery.